Incorporating the Benefits of Geosynthetic into MEPDG - Murad Abu-Farsakh; Mehdi Zadehmohamad; George Z. Voyiadjis (Infrastructures, 2023)
One of the most effective ways to increase the longevity of pavement structures is through the integration of geosynthetic reinforcement. Geosynthetics are synthetic materials such as geotextiles, geogrids, or geocomposites that are added to the interface between the subgrade and the base layer of a pavement structure. To evaluate the effect of various parameters on the structural benefits of geosynthetic reinforcement on the pavement structure of low-volume traffic flexible pavements, a finite element (FE) study was performed using the ABAQUS program. These parameters included the geosynthetic type, geosynthetic tensile stiffness, subgrade stiffness, and base thickness. The FE rutting curves for the 100 cycles were calibrated using the mechanistic–empirical (M-E) transfer functions, which were then used to calculate the long-term rutting curves. The traffic benefit ratio (TBR) was initially calculated based on the calibrated rutting curves for each pavement layer. The calculated TBRs were then used as an input in AASHTOWare to compute the base effective resilient modulus (MR-eff) and the factor of base course reduction (BCR). The results showed that adding one layer of geosynthetics enhanced the rutting performance of pavement structures significantly (up to 8.9 in TBR, 322% in MR-eff, and 64% in BCR). Geogrids showed higher benefits than geotextiles due to the interlocking between base aggregates and geogrid aperture. The values of TBR, MR-eff, and BCR increase with the increasing tensile stiffness of the geosynthetics and the rutting target and with the decreasing subgrade stiffness. The results also demonstrated peak values of TBR, MR-eff, and BCR for a base thickness of 25.4 cm.